PENGARUH ENTREPRENEURIAL ORIENTATION TERHADAP FINANCIAL PERFORMANCE MELALUI ORGANIZATIONAL LEARNING DAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PUBLIK SEKTOR MANUFAKTUR DI SURABAYA DAN SIDOARJO - Jessica Wijaya; Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the affect of entrepreneurial orientation, organizational learning and competitive advantage to the financial performance of go public manufacturing companies in Surabaya and Sidoarjo. The number of samples in this study were 30 go public manufacturing companies in Surabaya and Sidoarjo. Data obtained from the company samples were processed by using SmartPLS 2.0., in order to obtain the results that showed that there was a positive and significant affect of entrepreneurial orientation to financial performance and a positive and insignificant affect of organizational learning and competitive advantage to financial performance.